1990
DOI: 10.1180/claymin.1990.025.4.02
|View full text |Cite
|
Sign up to set email alerts
|

X-ray study of the nature of stacking faults in the structure of glauconites

Abstract: Glauconites are dioctahedral, microdivided, Fe-containing silicates whose idealized structure may be described as a stacking of 2 : 1 layers with the same azimuthal orientation. The diffractometric and crystallochemical data do not coincide with this idealized structural model. For each glauconite studied the best fit between experimental and theoretical XRD patterns was obtained using the same model. It was possible to describe the stacking by an equally probable occurrence of layers rotated by multiples of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 3 publications
1
29
2
Order By: Relevance
“…Note that the decomposition of the MiJ:+'sbauer spectrum of sample 68/69 was carried out by Dr Bonnin under conditions when Fe 3+ isomer shifts have been constrained to be equal. (Sakharov et al, 1990). In accordance with the diffraction features for dioctahedral tv 1M mica, XRD patterns contain strong lli, 112 and 112 reflections, whereas the 111 reflection has zero intensity.…”
Section: Mossbauer Spectra: Data Collectionmentioning
confidence: 63%
“…Note that the decomposition of the MiJ:+'sbauer spectrum of sample 68/69 was carried out by Dr Bonnin under conditions when Fe 3+ isomer shifts have been constrained to be equal. (Sakharov et al, 1990). In accordance with the diffraction features for dioctahedral tv 1M mica, XRD patterns contain strong lli, 112 and 112 reflections, whereas the 111 reflection has zero intensity.…”
Section: Mossbauer Spectra: Data Collectionmentioning
confidence: 63%
“…The mica-structure simulation program was applied to the study of the nature of stacking faults in glauconite and iUite structures using comparison of experimental diffraction curves with those calculated for structural models containing various defect types (Sakharov et al, 1990;Sakharov, 1991). Correct assignment of the atomic coordinates in the layer unit-cell was required to obtain satisfactory agreement between the intensity distributions in calculated and experimental XRD curves.…”
Section: Applicationsmentioning
confidence: 99%
“…Second, structural features are predicted and atomic coordinates are calculated, using a specially devised computer program, from the data on chemical composition and cell parameters of dioctahedral and trioctahedral micas having disordered cation distribution. Such calculations are useful to interpret infrared (IR), M6ssbauer and EXAFS spectroscopic data for monomineral samples, to simulate XRD patterns, and to aid in electrostatic energy calculations and estimations of O-H vector 9 1993 The Mineralogical Society orientation (Slonimskaya et al, 1986, Daynyak et al, 1984Drits & Tchoubar, 1990;Sakharov et al, 1990;Bookin et al, 1982).…”
mentioning
confidence: 99%
“…Even for samples that produce sharp reflections, it might not be possible to detect admixture of small amounts of either with large amounts of the other. Figure 6 compares the Potsdam illite with the Devonian Kalkberg K-bentonite (Reynolds and Hower, 1970) after heating to 350~ The two patterns are similar, although the broad 20/:I3/reflections for the Kalkberg sample indicate particle-size broadening, and the 02/: 11 l peaks are additionally broadened by n. 120 ~ rotational stacking disorder (n. 60 ~ disorder is minimal, based on 20l: 13l peak resolution, which is diminished by this type of disorder; see Sakharov et al, 1990). Patterns similar to those in Figure 6 have been reported by Reynolds (1992) for K-bentonites from the overthrust belt of Montana, though they were identified as 3T or twinned tv-lM polytypes; and diffraction patterns like that of the Potsdam illite have been noted for illites from the Rotliegendes (North Sea Basin) and Mount Simon (Illinois Basin) sandstones (Mingchou Lee, personal communication, 1992).…”
Section: Three-dimensional Structurementioning
confidence: 99%
“…Parameters for a 1M structure were obtained from the simultaneous solution of two expressions to give a, c, and ~ (Sakharov et al 1990). Drits et al (1984) is shown by Table 3.…”
Section: Three-dimensional Structurementioning
confidence: 99%